2021
DOI: 10.3748/wjg.v27.i18.2131
|View full text |Cite
|
Sign up to set email alerts
|

Remaining issues of recommended management in current guidelines for asymptomatic common bile duct stones

Abstract: Current guidelines for treating asymptomatic common bile duct stones (CBDS) recommend stone removal, with endoscopic retrograde cholangiopancreatography (ERCP) being the first treatment choice. When deciding on ERCP treatment for asymptomatic CBDS, the risk of ERCP-related complications and outcome of natural history of asymptomatic CBDS should be compared. The incidence rate of ERCP-related complications, particularly of post-ERCP pancreatitis for asymptomatic CBDS, was reportedly higher than that of symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Unfavourable outcomes in the observation cohort also included complications post‐ERCP complications for patients initially observed, who then became symptomatic. This was not included in the unfavourable outcomes of treatment strategies and may underestimate the rate of ERCP complications 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfavourable outcomes in the observation cohort also included complications post‐ERCP complications for patients initially observed, who then became symptomatic. This was not included in the unfavourable outcomes of treatment strategies and may underestimate the rate of ERCP complications 23 …”
Section: Discussionmentioning
confidence: 99%
“…This was not included in the unfavourable outcomes of treatment strategies and may underestimate the rate of ERCP complications. 23 Four of eight included studies favoured an observation-based approach, [15][16][17][18] albeit with relatively small sample sizes (total 196 patients). Two studies do not make a clear recommendation in relation to a policy of observation.…”
Section: Discussionmentioning
confidence: 99%
“…ERCP-ES and subsequent LC, the most preferred method worldwide[ 4 , 17 , 50 ], is a safe management process even in patients with cardiovascular disease[ 51 ]. A randomized controlled study showed that routine nasobiliary tubes after endoscopic CBD stone clearance can facilitate subsequent LC by the ability of the intraoperative cholangiography and ensure the anatomical integrity of the CBD[ 52 ].…”
Section: Managementmentioning
confidence: 99%
“…For asymptomatic CBD stones, ERCP-ES is the first choice of recommended management despite the higher complication rate, especially of acute pancreatitis, than that of symptomatic cases. However, it is not yet clear by evidence-based data that this approach is justifiable[ 50 ]. The opposite point of view postulates by assessing the natural history that while early endoscopic removal of silent stones does not absolutely prevent further biliary complications, it has the risk of post-ERCP severe pancreatitis (5.2%).…”
Section: Managementmentioning
confidence: 99%
“…Therefore, given the high incidence of AEs, it should be carefully considered whether aggressive ERCP should be performed for asymptomatic CBDS. 12 In cases of CBDS with surgically altered anatomy, the treatment of choice is ERCP, as in cases with normal anatomy; however, the ERCP is assisted by balloon-enteroscopy (BE) in cases of surgically altered anatomy due to the increased distance from the afferent loop to the duodenal papilla. [13][14][15][16] In a Japanese multicenter cohort study, which included our facility, the success rate of BE-assisted ERCP cannulation for surgically altered anatomies (76.3% were benign biliary cases, including CBDS) was 87.0%, with an AE rate of 7.7% (PEP rate was 3.1%), 17 making it an effective treatment method similar to that for normal anatomies.…”
Section: Introductionmentioning
confidence: 99%